Production Cost Management In The Development Of Karawo Center At Smes Of Karawo Business Source Mongolato Village, Gorontalo Regency - Didin Lonto; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (Cita konsultindo, 2026)
The Karawo Center in Gorontalo Regency has an important role in the development of a creative industry based on local culture. Although the demand for Karawo products tends to increase, the management of production costs at the Small and Medium Industries (SMEs) scale still faces various obstacles, especially related to efficiency and cost control. This study aims to analyze the application of production cost management strategies based on the management function of Planning, Organizing, Actuating, and Controlling (POAC) in Karawo Business Source SMEs in Mongolato Village, Gorontalo Regency.This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research informants include business owners, production managers, and Karawo craftsmen. The data was analyzed by examining the application of POAC functions in managing raw material costs, labor, and overhead costs. The results of the study show that production cost management is still carried out simply and has not been integrated into a systematic management function. Cost planning has not been carried out before production, labor organization has not been optimal, production implementation still causes inefficiencies, and cost control has not been implemented in a sustainable manner. This study concludes that the implementation of POAC-based production cost management can be an important strategy in increasing efficiency and supporting the sustainable development of the Karawo Center.